يوتوبيا لخالد توفيق .. معمار روائي يقاوم انهيار القيم وخراب الروح - الأبيض, رضا (University of Eloued جامعة الوادي, 2017)
يركز هذا المقال على العلاقة الإبداعية بين شكلين من الفن هما العمارة والرواية. يستكشف، أولا، الأساسات النظرية التي تقوم عليها هذه العلاقة تأثيرا وتأثرا وتشابها وتناظرا .. من خلال الاهتمام ببعض الخصائص المشتركة لكلا الشكلين الفنيين: الصورة والمكونات .. والتي سوف تدرس من أجل تعميق التفكير في هذه العلاقة . وفي القسم الثاني من العمل يتم النظر في رواية "يوتوبيا" لتوفيق أحمد خالد ( 2008) لاستجلاء مظاهر التداخل بين الرواية والعمارة : معمار الرواية / المعمار في الرواية .. إن "يوتوبيا" رواية مستقبلية. فزمن قصتها عام 2023، في مصر التي انقسمت إلى طبقتين الأولى غنية جدا تعيش في جزء من المدينة، تحميها الجدران العالية ومشاة البحرية الأمريكية.. في حين يعيش بقية السكان الفقراء في الأحياء الفقيرة . إنهم الآخرون الغرباء الذين صار صيدهم لعبة لتمضية الوقت وقتل الملل.. إن من خصائص هذه الروية التناوب والتناظر بين رؤيتين للعالم وفضاءين ومعمارين .. يفصل بينهما جدار يرمز إلى المستقبل المأساوي .. في نهاية هذه الدراسة ينتهي تحليل التشابه بين بنية الرواية وبنية المعمار فيها إلى تأكيد أن "يوتوبيا " رواية تعكس رؤية جمالية حداثية وموقفا إيديولوجيا متشائما لكنه يقاوم السقوط الأخلاقي والثقافي This essay focuses on the creative relation between two forms of art, architecture and the novel. First, this essay explores the fundamentals of analogy. Characteristics common to both forms of art : notions of image and composition.. will be studied in order to feed the reflection on this subject The second part applies the foundations drawn from this analogy to the novel Utopia written by Ahmed Khaled Tawfiq ( 2008) Utopia is the future. we are in Egypt in 2023, and, after a division of classes, the very rich live in a part of the city, protected by high walls and ancient American marines. High security for the very rich while the rest of the populace, the poor, live in slums, these are the Others. What is interesting in this novel is the alternation and symmetry between two visions of the world, tow places and tow architectures . but The two worlds are separated by a wall. Which indicates that the wall symbolizes the tragic future. Ahmed Towfik describes a society (both inside and outside) in a dark vision of today, black of the future In the end, the analysis of this analogy: architecture of the novel and architecture in the novel demonstrate that Utopia reflects a modern aesthetic vision and a pessimistic ideological position that resists the cultural and moral fall.
Keywords: رواية، معمار، يوتوبيا، تناظر، صراع طبقي، ديستوبيا; novel, Architecture, Utopia, symmetry, Conflict between classes, Destopia